Strategies on halal certification obligations: Learning from the experience of LPPOM MUI South Sulawesi - Sofyan, Andi Syathir; Nur, Awal; Sofyan, Syaakir; Ulum, Bahrul (International Journal of Halal Industry, 2025)
Purpose – Since 2019, halal inspection institutions (LPH), other than the LPPOM MUI, have been newly formed. faced issues of sentiment towards halal certification and the experience gap between LPH and LPPOM MUI. This research aims to predict registrants for halal product certification at LPPOM MUI South Sulawesi from sentiment on social media and to identify strategies to increase it. Methodology – The first method used is ARIMAX for halal certification registrants regarding halal logo trends on Google Trends, and the second is SWOT analysis, which continues with the Analytical Hierarchy Process (AHP). Findings – Based on the results of the ARIMAX analysis of order (0,0,1), there is no significant relationship between the sentiment variables towards halal certification registrants at LPPOM MUI South Sulawesi. The results of the SWOT analysis concluded that LPPOM MUI South Sulawesi is in Quadrant IV, namely on the defensive side, which is unprofitable. For this reason, based on AHP analysis, it is necessary to make improvements in increasing halal awareness for the community, especially for businesspeople and MSMEs. Implications – This research has implications for the development of strategies at the LPPOM MUI and LPH institutions in increasing halal certification registrants through analysis results. Originality – This paper provides novel insights into the development of the halal industry through strategic steps, as well as the results of forecasting the number of applicants for halal certification with sentiment towards it, where there is very little research that examines forecasting in the halal industry sector.